2017
DOI: 10.1111/joic.12444
|View full text |Cite
|
Sign up to set email alerts
|

Imaging behind occluded areas with an iatrogenic perforated balloon: A safe, practical, and simple new method of visualizing the distal lumen in total occlusion

Abstract: This new method we developed is much simpler and more useful than other methods for visualization of the true lumen because we can re-orient the balloon at the time of opaque injection and use 190 cm guidewire without additional costs. Additionally, one balloon is sufficient for the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…With this drilled balloon, by moving it, “back and forth” over the guide wire, opaque was given to visualize the entire region of the lesion extensively. We call this as “true lumen test,” that reveals the properties and location of the lesion . Thrombi was aspirated in patients that had such.…”
Section: Methodsmentioning
confidence: 99%
“…With this drilled balloon, by moving it, “back and forth” over the guide wire, opaque was given to visualize the entire region of the lesion extensively. We call this as “true lumen test,” that reveals the properties and location of the lesion . Thrombi was aspirated in patients that had such.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous publication about the first application, which we termed the “True Lumen Test” in which opaque agent was delivered to the distal through a perforated balloon in order to show the occluded coronary distal, we have described how the balloon was perforated and used for this purpose. In addition, we compared this application with Over the Wire (OTW) balloon, and demonstrated that this method is more advantageous and has less side effect profile and a lower cost compared to the OTW balloon application …”
Section: Discussionmentioning
confidence: 99%
“…The use of a perforated balloon to deliver local NTG to a precise location at higher doses has not yet been studied. In our previous study, we demonstrated that the visualization of the distal of total occlusion with an iatrogenic perforated balloon is a safe, practical, and simple method . In this study, we aimed to compare intracoronary NTG injection with the catheter administration of NTG to the spasm area with an external iatrogenically perforated balloon in patients who developed vasospasm during coronary angiography or coronary angioplasty.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently read with great interest the manuscript by Balaban et al describing a new method for distal vessel visualization by a perforated monorail balloon catheter. 1 Thanks a lot to the authors for this valuable study. They reported that they were successfully visualized distal vascular bed in a total of 63 patients with acute or chronic total occlusions with this new method.…”
Section: Off-label Utilization Of Monorail Balloon Cathetersmentioning
confidence: 99%
“…The usage of some special coronary perfusion catheters and over the wire balloon catheters have been described for this purpose. [2][3][4] We have previously used the method described by Balaban et al 1 for relieving no reflow in acute myocardial infarction patients. 5 In our experience, this method is a good tool for visualizing the distal vascular bed and in addition we used this method for treating no reflow.…”
Section: Off-label Utilization Of Monorail Balloon Cathetersmentioning
confidence: 99%